Clinical and anamnestic, pre- and intraoperative predictors of maternal and neonatal complications of cesarean section - I. Z. Gladchuk; Yu. V. Herman; D. O. Hryhurko (Kazimierz Wielki University, 2019)
The progressive decline in the world population's health index causes the need for a comprehensive set of measures to ensure the safety of caesarean section. There are a number of purely technical problems, the solution of which largely depends on the outcome of the operation for the mother and the fetus. In spite of the technical simplicity of caesarean section, this is a cavitary operation and should be classified as complex surgical interventions, with possible intraoperative and postoperative complications. The aggregate index of the incidence of intraoperative, early and late complications of abdominal rozdorosheniya varies widely within the range - from 4.5 to 18.5% [1, 2]. The incidence of obstetric and perinatal complications is directly related to the increase in the frequency of cesarean section. The group of increased risk of operational degeneration include: first-born babies, patients with obstructed obstetric history, pregnant women with scarring on the uterus after cesarean section, women with multiple pregnancy, preeclampsia, extragenital and genital diseases. The identification of some important clinical and anamnestic, pre- and intraoperative predictors of prenatal risk can significantly reduce the incidence of possible complications during abdominal delivery, as well as improve maternal and perinatal outcomes during the later postoperative periods.